Students’ Strategies for Achieving Publication in SINTA-Accredited Journals - Hasnah Faizah; Rahmi Septia Frisye; Siti Andriana (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
This study aims to identify and analyze students’ strategies in achieving publication in SINTA-accredited journals. The research employs a qualitative approach with a descriptive design. Data were collected through in-depth interviews, observations, and digital documentation involving students who have experience in the scientific publication process. Data analysis was conducted using the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The findings reveal that students’ strategies are integrated into three main stages: research planning, scientific writing, and the publication process. In the planning stage, students are publication-oriented from the beginning by selecting relevant topics and conducting intensive literature reviews. In the writing stage, students adapt their articles to journal templates, improve academic language skills, utilize reference management tools, and perform iterative revisions. In the publication stage, students understand the use of the Open Journal System (OJS), select journals that align with the scope, and respond constructively to reviewers’ comments. Additionally, this study identifies several challenges, including limited understanding of the publication system, publication costs, lengthy editorial processes, and mismatches in journal scope perception. Academic resilience emerges as a crucial factor in dealing with rejection and increasing the chances of publication success.